TEACHING POETIC METERS TO SENIOR HIGH SCHOOL STUDENTS - Nuraliyeva Sevinchbonu (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article provides information on effective methods and methodologies for teaching poetic meters to senior high school students. It covers the theoretical foundations of poetic meters, didactic materials used in the learning process, and practical exercises. Additionally, the article offers methodological recommendations aimed at increasing students’ interest in poetry and developing their artistic thinking.